Earliness, yield and bulb parameters of hardneck garlic (Allium sativum L.) as influenced by leaf knotting and scape removal in north Indian plains - Sekhon, N Garg, K S (Journal of Spices and Aromatic Crops, 2016)
The present study was conducted during Rabi 2012–13 and 2013–14 to estimate the effect of scape removal, leaf knotting 4 weeks before harvest and leaf knotting 2 weeks before harvest on earliness, yield and bulb parameters of hardneck garlic cultivar ‘PG-17’ in north western plains of India. The removal of scapes has no effect on reduction in days to maturity, equatorial diameter of bulb, bulb weight, number of cloves per bulb and cured bulb yield as compared to control. The knotting of leaves 4 and 2 weeks before harvest advanced maturity by 12 and 6 days, respectively, over control. Leaf knotting 4 weeks before harvest significantly decreased equatorial diameter of bulb, bulb weight and cured bulb yield, whereas, leaf knotting 2 weeks before harvest caused non-significant reduction in equatorial diameter of bulb, bulb weight, number of cloves per bulb, 50-clove weight and cured bulb yield as compared to control. It is therefore advisable that the practice of leaf knotting may be omitted to save labour charges, whereas the practice of scape removal in hardneck garlic cultivars should be exercised only after studying the response of that particular cultivar to scape removal.